Marknaden för skogsvårdstjänster : en undersökning bland privata markägare inom en region i Värmland - Andersson, Lars (SLU/Dept. of Forest Resource Management, 2008)
This work broadly illuminates the conditions for increasing the commissions of forestry services within the whole, or parts of, the western regions of Stora Enso's operating area. Through a questionnaire, a survey was made examining whether the owners of the forests themselves do the forestry on their woodlands. This foremost concerns the pre-commercial thinning, but also planting and soil scarification. The survey also shows who are buying the most part of their forestry services and who are carrying it out themselves. Further on, the work clarifies differences in buying forestry services in view of the owner's age, size of property and whether the owner lives in or out of the municipality that the owned forest is situated in.